2002
DOI: 10.2166/wst.2002.0633
|View full text |Cite
|
Sign up to set email alerts
|

Regional planning and product recovery as tools for sustainable sludge management

Abstract: The article presents two aspects of sludge management: regional planning and product recovery. The introduction of these two elements can reduce the cost, close the ecocycle and make the management more sustainable. A spreadsheet program to optimize the regional location of different facilities is presented. The simple example shows the potential of the model. The brief comparison of formal problems concerning sludge disposal in Poland and Sweden is also discussed. Requirements of phosphorus recovery and recyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Process inefficiencies were considered as opportunities for the company to achieve, simultaneously, environmental and economic benefits. The impacts of those improvements were evaluated in terms of starch recovery, water consumption, oil and grease recovery, and WWTP optimisation, providing empirical evidence that source separation technologies can play a crucial role (in accordance to Wilsenach et al [18] and Stypka et al [19]). Particularly product recovery enabled the company to reduce industrial costs, by reducing the negative impacts of effluents upon the ecological cycles, therefore contributing to a more sustainable management of the production processes.…”
Section: Discussionmentioning
confidence: 91%
“…Process inefficiencies were considered as opportunities for the company to achieve, simultaneously, environmental and economic benefits. The impacts of those improvements were evaluated in terms of starch recovery, water consumption, oil and grease recovery, and WWTP optimisation, providing empirical evidence that source separation technologies can play a crucial role (in accordance to Wilsenach et al [18] and Stypka et al [19]). Particularly product recovery enabled the company to reduce industrial costs, by reducing the negative impacts of effluents upon the ecological cycles, therefore contributing to a more sustainable management of the production processes.…”
Section: Discussionmentioning
confidence: 91%
“…They concluded that biological treatment should be applied if the main objective was lowest possible emissions, and that control at source was necessary to avoid heavy metals and toxic organic compounds in the sludge produced. Stypka et al (2002) presented two aspects of sludge management: regional planning and product recovery. They developed a spreadsheet program to optimize the regional location of different facilities.…”
Section: Regulations and Biosolids Management Planningmentioning
confidence: 99%